Why bother getting involved? Commitment and mobilisation within current climate and environmental movements - Nørholm Lundin , Anna (Adult Education Discourses, 2022)
The present article analyses mobilisation in climate and environmental movements as a social practice. The research questions concern why people take part in said movements, and how this makes sense to them, in relation to the specific context. The study aims to understand participation on several levels, thus filling knowledge gaps regarding the cross-section of civil society, social movements and Bourdieu’s theory of social practices. The empirical study consists of two cases of current climate and environmental movements. The first case concerns local groups and networks mobilised to preserve forests and parks. The second case concerns local and global climate strikes and manifestations. The reasons for taking part in such movements are found on several levels. Firstly, the explicit concerns and cares, as well as frustrations, trigger the commitment. Taking part is a way to handle the crisis in a way that makes sense personally. Secondly, previous experiences, education and professional life enable a sense of belonging and a sense of being able to take part. Thirdly, the socialisation that takes part within the social practice contributes to an increased commitment. In the stories about previous and coming actions, values and traditions – of the right ways of doing and being – a practical sense/habitus for this social practice is reproduced. The conveying of concerns in public is understood and explained as a ritualised practice, contributing to the commitment, as a key resource.